A new heat transfer correlation suited for the design of fixed-bed reactors via numerical optimization - Pietschak, Alexander; Dixon, Anthony G.; Freund, Hannsjörg (Chemical Engineering Science, 2020)
A new correlation to account for the radial heat transfer in fixed-beds modeled via a 2D pseudo-homogeneous approach is presented in this contribution. Compared to state-of-the-art heat transfer correlations, no points of discontinuity are included in the definition of the new heat transfer correlation. This enables a direct application of gradient-based solution algorithms for the reactor design via numerical optimization. The presented heat transfer correlation is based on individually considering the influence of the radial velocity profile and radial bed voidage profile in the fixed-bed on the heat transfer. The predictive performance of the presented heat transfer correlation is benchmarked against the state-of-the-art heat transfer correlation proposed by Winterberg et al. for both, spherical and cylindrical shaped particles, based on an evaluation of a broad measurement data basis from literature heat transfer experiments.
CRIS-Team Scopus Importer:2020-03-20
Keywords: Catalytic fixed-bed; Heat transfer; Numerical optimization; Reactor design; Transport phenomena